Meeting the challenge of crime in the global village: an assessment of the role and future of the United Nations Commission on Crime Prevention and Criminal Justice - Ram, Christopher D. (Publication series, 2012)
This book examines recent developments in the evolution of crime at the domestic and transnational level, the pressures that these have exerted on domestic law and policy and national sovereignty, and the effectiveness of the United Nations Commission on Crime Prevention and Criminal Justice as a collective response to those pressures. At the time of writing (April - December of 2011) the Commission, which was established in 1992, is in its 20th year, and a re-assessment is in order. In order to evaluate the effectiveness of the Commission, it is necessary to first assess the various functions it performs, whether by design or not, and the value of these functions to the Member States individually and the international community as a whole. This is more complex than it may seem, because effectiveness is largely in the eye of the beholder and must inevitably be assessed as against the expectations of the many different constituencies it serves, which are defined not only by national or regional economic, political or other substantive interests but also in terms of the diplomatic, criminological, security, development and intergovernmental, governmental or non-governmental lenses through which various participants perceive the Commission and its work. In this context, the book then considers developments of the past two decades and the perspectives of various constituencies on what has worked and what has not. It concludes that the benefits of the Commission and the work it mandates are, while often abstract, long-term and difficult to quantify, substantial when compared with the relatively small investment it demands from the Member States. At the 20th session, held in April 2011, the frustrations of many delegations appeared to crystallise in a new will to adopt procedural reforms, which bodes well for the future, but the Commission was also advised of major resource limits that will reduce the documentation by the Commission of its work, which bodes ill. These and other recent developments will be considered with a view to developing ideas and proposals for the future.